The Attachment of Leadership and Followership that Prioritizes Integrity in Realizing an Anti-Corruption Organization - Iftitah Rizky Dewi; Muhamad Fuad Budi Syakir (Asia Pacific Fraud Journal, 2022)
Humans play an important role in an organization. Humans, according to their responsibilities in an organization, are divided into leaders and followers. Both leaders and followers create a dynamic environment that produces organizational culture. This paper aims to emphasize the imperative need for leaders and followers to act with integrity. Tone at the top has proven to be an effective antidote to corruption, while followers must also be able to protect their leaders from asymmetric information that could lead them to unfair decisions. The method used in this paper is a literature study and comparative analysis applied in private companies in South Tangerang and public offices in Jakarta. The results of this study demonstrate the importance of integrity for both leaders and followers in achieving an anti-corruption organization.